Optimization of a Recombinant Lectin Production in Pichia pastoris Using Crude Glycerol in a Fed-Batch System - Dulce Palmerín-Carreño (Processes, 2021)
The production of heterologous proteins for medical use is an important area of interest. The optimization of the bioprocesses includes the improvement of time, costs, and unit operations. Our study shows that a lectin fraction from Tepary bean (Phaseolus acutifolius) (TBLF) has cytotoxic effects on colon cancer cells and in vivo antitumorigenic activity. However, the low-yield, time-consuming, and expensive process made us focus on the development of a strategy to obtain a recombinant lectin using engineered Pichia pastoris yeast. Pure glycerol is one of the most expensive supplies; therefore, we worked on process optimization using crude glycerol from biodiesel production. Recombinant lectin (rTBL-1) production and purification were evaluated for the first time by an experimental design where crude glycerol (G65) was used and compared against pure glycerol (G99) in a controlled stirred-tank bioreactor with a fed-batch system. The recombinant lectin was detected and identified by SDS-PAGE, Western blot, and UHPLC–ESI–QTOF/MS analysis. The results show that the recombinant lectin can be produced from G65 with no significant differences with respect to G99: the reaction rates were 2.04 and 1.43 mg L−1 h−1, and the yields were 264.95 and 274.67 mgL−1, respectively. The current low cost of crude glycerol and our results show the possibility of producing heterologous proteins using this substrate with high productivity.